Practical applications of synthetic biology (Invited Lecture) - Rodrigues, Joana Lúcia Lima Correia (2024)
Advanced Molecular Biotechnology Curricular Unit, Master in Biotechnology and Master in Chemical and Biological Engineering, University of Minho.